POTENSI FISKAL TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT - Luqman Khakim; Iwan Hermawan; Achmad Solechan; VS Tripriyo PS (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
This research objectives are first, to determine the influence of potential fiscal (local revenue, general allocation fund, sharing fund, and other official local revenues) to local economic growth. Second, to study potential fiscal impact and local economic growth to its society welfare. The study took all population as it samples (116 cities in Java), ie: local budget realization of all cities in Java from 2007-2009 and uses panel data. Lisrel 8.54 is employed to analyze to form Structural Equation Modeling. The result shows that first, local revenues and sharing fund have positive influence to economic growth, while general allocation fund and other local revenues influence negatively to economic growth. Second, local revenues, general allocation fund and sharing fund have positive impact on local society welfare, while the other local revenues have no significant impact on it.